All Digital Spread Spectrum Clock Generator for EMI Reduction. - Damphousse, S.
An effective solution to control electromagnetic interference in computing appliances such as DVD players or home theater systems is to apply modulation on the system clock. The presence of modulation on the clock reduces the radiated power per unit bandwidth. We present the implementation of a spread spectrum clock generator (SSCG) using strictly digital components. A digital delay line (DDLi) controlled by a small digital circuit is used to increase or decrease the delay on a clock and hence create a modulated output. The DDLi total electrical length is no longer than one period of the 27-MHz reference clock as the digital circuit can adjust to the limited length of the line. The circuit can produce up or down spread by modulating the frequency of the reference with a triangular waveform. The measured peak power reduction is greater than 13 dB for a deviation of about 3% and a frequency modulation of 100 kHz. A real-time digital calibration circuit enables a process and temperature independent operation. The circuit occupies 0.06 mm2 in a 0.15-mum CMOS process and consumes 7.1 mW
Keywords: 0.15 micron; 100 kHz; 27 MHz; 7.1 mW; CMOS process; EMI reduction; All digital spread spectrum clock generator; Digital circuit; Digital delay line; Electromagnetic interference; Frequency modulation; Real-time digital calibration circuit; Reference clock; System clock; Triangular waveform